2014
DOI: 10.5001/omj.2014.90
|View full text |Cite
|
Sign up to set email alerts
|

VanA and VanB Positive Vancomycin-resistant Staphylococcus aureus Among Clinical Isolates in Shiraz, South of Iran

Abstract: The results showed that the frequency of vancomycin resistance genes (vanA, vanB) is very high in Staphylococcus aureus strains isolated from patients in south of Iran. Thus, urgent interventions are needed to keep the emergence and transmission of these isolates to a minimum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…In this study, a positive relation was observed between phenotypic and PCR results for the determination of antimicrobial resistance which is in agreement with Gao et al [29] and Saadat et al [50] . However, Zmantar et al [28] and Salih et al [51] reported no correlation between phenotypic and PCR methods.…”
Section: Tetk-1 Tetksupporting
confidence: 81%
“…In this study, a positive relation was observed between phenotypic and PCR results for the determination of antimicrobial resistance which is in agreement with Gao et al [29] and Saadat et al [50] . However, Zmantar et al [28] and Salih et al [51] reported no correlation between phenotypic and PCR methods.…”
Section: Tetk-1 Tetksupporting
confidence: 81%
“…The acquisition and spread of vanZ genes in S. aureus could become a critical problem. The vanZ Tei, gene, as a part of the vanA gene cluster, is occasionally transferred from enterococci into S. aureus, leading to highly vancomycin-resistant strains (VRSA) (Chang et al, 2003;Perichon and Courvalin, 2009;Saadat et al, 2014). Although the incidence of such an event remains low, apparently due to the high fitness cost of vanHAXmediated resistance in S. aureus (Foucault et al, 2009), VRSA strains may represent progenitors for the generation of vanZ Teicarrying mobile genetic elements.…”
Section: Discussionmentioning
confidence: 99%
“…[22] After that, several VRSA isolates confirmed by genetic analysis have been reported from different countries such as US, India, Pakistan, and Iran. [23] In Imam Khomeini Hospital in Tehran, Aligholi et al . identified 2 (0.56%) strains of VRSA confirmed by minimum inhibitory concentration of 64 and 512 mcg/ml for vancomycin as well as detection of vanA gene in 1 of the isolates through polymerase chain reaction (PCR).…”
Section: Discussionmentioning
confidence: 99%
“…[17] Agar screening and PCR tests on 220 staphylococcal samples from three laboratories of Shiraz hospitals (Shahid-Faghihi, Namazi, and MRI) between March and December 2012 demonstrated that vanA and vanB resistant genes were positive in 34% and 37% of clinical isolates, respectively. [23] The development of VRSA could be attributed to overuse and selective pressure of vancomycin. In this regards, results of a cross-sectional study in a referral university-affiliated hospital in Shiraz at 2003 revealed that the prescription of vancomycin was only appropriate in 12 out of 200 (6%) patients according to the Hospital Infection Control Practice Advisory Committee guideline.…”
Section: Discussionmentioning
confidence: 99%